A general approach to deriving diagnosability results of interconnection networks*. Issue 4 (4th July 2022) - Cheng, Eddie; Mao, Yaping; Qiu, Ke; Shen, Zhizhang
Abstract : We generalise an approach to deriving diagnosability results of various interconnection networks in terms of the popular g -good-neighbour and g -extra fault-tolerant models, as well as mainstream diagnostic models such as the PMC and the MM* models. As demonstrative examples, we show how to follow this constructive, and effective, process to derive the g -extra diagnosabilities of the hypercube, the ( n, k ) -star, and the arrangement graph. These results agree with those achieved individually, without duplicating structure independent technical details. Some of them come with a larger applicable range than those already known, and the result for the arrangement graph in terms of the MM* model is new.